Digitalized Everyday Past: History of Everyday Life Database - Vojtěch Kessler; Jan Bouška (Colloquia Humanistica)
The article presents the international digital humanities project called History of Everyday Life Database and its possibilities for use in humanities research. The foundations of this project, which is run by the Institute of History of the Czech Academy of Sciences, were laid in the 1990s. Its main goal is to form a digital collection of sources (mainly biographical documents) on the history of “everyday life”. The database includes hundreds of such sources in the Czech and German languages and makes them accessible to scholars, students and the public, helping them get a different perspective on the past, one that was not shaped only by “great history”. The project also aims to create an interdisciplinary platform for mutual discussion and a common research space for scholars dealing with the topics of the history of everyday life and memory studies.